Self-assembly of dendritic DNA into a hydrogel: application in three-dimensional cell culture - Wu, Jingyuan (2022)
With inherent biocompatibility, biodegradability, and unique programmability, hydrogels with a DNA framework show great potential in three-dimensional (3D) cell culture. Here, a DNA hydrogel was assembled by a dendritic DNA with four branches. The hydrogel showed tunable mechanical strength and reversible thixotropy even under a nanomolar DNA concentration. The cell culture medium can be converted into the hydrogel isothermally at physiological temperature. This DNA hydrogel allows both cancer and somatic cells to be seeded in situ and to achieve high proliferation and viability. The bis-entity of dendritic branches enabled the specific loading of bioactive clues to regulate cell behaviors. Thus, the dendritic DNA-assembled hydrogel could serve as a highly biocompatible, readily functionalizing, and easy-casting gel platform for 3D cell culture.